Prospects for the implementation of a bachelor’s degree in medicine - O. V. Sirotkina; T. N. Ischuk; I. S. Golubeva; E. V. Parmon; E. V. Shlyakhto (Российский кардиологический журнал)
According to modern healthcare requirements, it is necessary to increase workforce capacity of primary care practice, therefore, improving the specialist training is one of the high-priority problems of medical education. Not enough attention is paid to paramedic education and their role in Russian healthcare. The presented analysis of the paramedic profession history and the current state of high-quality healthcare in Russia shows the need to create a regulatory basis for the training of paramedics in the higher education system — a bachelor’s degree.